Analisis Implementasi Pendidikan Karakter Di Pondok Pesantren Aisyah Samawa, Sumbawa Besar, NTB - Walidain, Sri Nurul; Fitriyanto, Syarif; Ardianti, Suji (Jurnal Literasi dan Pembelajaran Indonesia, 2022)
Various new problems that are growing in the world of education are certainly a challenge for education experts and education activists to find patterns of superior character education. This study aims to analyze the implementation of character education as an effort to prevent the moral disruption of students in Islamic boarding schools. The cultivation of spiritual values ​​that are in line with the teachings of Islam is very fundamental in building the character and civilization of a nation. This study uses a qualitative approach with a descriptive type. This research was conducted at the Aisyah Samawa Islamic Boarding School. Collecting data using interview and observation techniques. Data analysis using interactive analysis techniques. The results of the research and data analysis show that the success of educational activities in building a character (morals) must be integrated from several essential components, namely curriculum, learning methods, and strengthening learning activity programs in strengthening Islamic character. Aisyah Samawa Islamic Boarding School tries to present a fun learning model based on the Al-Quran and as-Sunnah. This Islamic boarding school offers an educational concept that has implications for improving the character of students.